Escalate and De-Escalate Therapies for Intracranial Pressure Control in Traumatic Brain Injury - Battaglini, Denise; Anania, Pasquale; Rocco, Patricia R. M.; Brunetti, Iole; Prior, Alessandro; Zona, Gianluigi; Pelosi, Paolo; Fiaschi, Pietro (Frontiers in Neurology, 2020)
Severe traumatic brain injury is frequently associated with an elevation of intracranial pressure (ICP), followed by cerebral perfusion pressure (CPP) reduction. Invasive monitoring of ICP is recommended to guide the step-by-step “staircase approach” which aims to normalize ICP values and reduce the risks of secondary damage; however, if such monitoring is not available clinical examination and radiological criteria should be used. A major concern is how to taper the therapies employed for ICP control. The aim of this manuscript is to review the criteria for escalate and taper therapies in traumatic brain injury (TBI) patients. Each step of the staircase approach carries a risk of adverse effects related to the duration of treatment. Tapering barbiturates should be started once ICP control has been achieved for at least 24 hours, although a period of 2-12 days is often required. Administration of hyperosmolar fluids should be avoided if ICP is normal. Sedation should be reduced after at least 24 h of controlled ICP to allow neurological examination. Removal of invasive ICP monitoring is suggested after 72 h of normal ICP. For patients who have undergone surgical decompression, cranioplasty represents the most aggressive step, and an earlier cranioplasty (15-90 days after decompression) seems to reduce the rate of infection, seizures, and hydrocephalus.